2021
DOI: 10.1039/d1ta02812j
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable thermoelectric property enhancement in Cu2SnS3–CuCo2S4 nanocomposites via 3D modulation doping

Abstract: P-type ternary sulfide Cu2SnS3 and CuCo2S4 with merits of low toxicity, natural abundance and intrinsic low lattice thermal conductivity are considered as promising eco-friendly thermoelectric materials. Here, we report a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…In this temperature range, sulphides of copper and tin or copper and iron can be viable alternatives. Gu et al [14] discussed 3D modulation doping of CuCo 2 S 4 in CTS and reported a zT ~0.82 at 773 K. Zhao et al [15] reported simultaneous Co and Sb substitution in the CTS system resulting in a zT of ~0.88 at 773 K. Furthermore, Deng et al [16] reported a zT of ~1 in a similar Cu 7 Sn 3 S 10 system through Br-doping. A zT of ~0.4-0.8 above 700 K is regularly reported for CTS by In [17], Zn [7], Mn [18], Ni [19], Fe [20], Co [21], and Cu [22] substitution at the Sn site, aiming to enhance the carrier concentration and reduce the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this temperature range, sulphides of copper and tin or copper and iron can be viable alternatives. Gu et al [14] discussed 3D modulation doping of CuCo 2 S 4 in CTS and reported a zT ~0.82 at 773 K. Zhao et al [15] reported simultaneous Co and Sb substitution in the CTS system resulting in a zT of ~0.88 at 773 K. Furthermore, Deng et al [16] reported a zT of ~1 in a similar Cu 7 Sn 3 S 10 system through Br-doping. A zT of ~0.4-0.8 above 700 K is regularly reported for CTS by In [17], Zn [7], Mn [18], Ni [19], Fe [20], Co [21], and Cu [22] substitution at the Sn site, aiming to enhance the carrier concentration and reduce the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hall carrier concentration dependence on the room-temperature Seebeck coefficient of n-type cast Bi 2– x /3 Cr x /3 S 3– x Cl x compared to those reported in the literature of Bi 2 S 3 doped with BiCl 3 , LaCl 3 , CuBr 2 , and Cl …”
Section: Resultsmentioning
confidence: 94%
“…A series of band structure engineering approaches have also been employed to improve the power factor of TE materials. Strategies such as quantum confinement, modulation doping, and energy filtering , are being actively pursued.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of modulation doping, the secondary phase increases the conductivity by donating electrons to the host semiconductor, while in the case of energy filtering, the secondary phase scatters electrons and reduces mobility. The thermoelectric research community has also used this mechanism to enhance the thermoelectric performance of materials [15,23,25,29,38]. For thermoelectric materials, a combination of two effects has enhanced the thermoelectric efficiency in the modulated doped materials: firstly, a large increase in the electrical conductivity and mobility of the charge carriers [130], and secondly, a reduction in the lattice thermal conductivity as a result of the scattering of phonons by nanostructuring [23,131].…”
Section: Modulation Dopingmentioning
confidence: 99%
“…A series of band structure engineering approaches have also been employed to improve the electronic properties [18][19][20]. Strategies such as quantum confinement [21,22], modulation doping [23][24][25], introducing resonance energy to the electronic density of states [26,27], and energy filtering [28] are being actively pursued. These strategies are adopted to modify the band structure and transport properties of the thermoelectric materials by either tuning the electrical conductivity and the Seebeck coefficient independently or by increasing them simultaneously.…”
Section: Introductionmentioning
confidence: 99%